Preliminary Outcomes of Calcaneal Body Lengthening for the Calcaneus Shortening - Yidong Cui; Qingjia Xu; Jiancheng Zang; Gang Wang; Ben Liu; Bin Chen; Junhao Lin; Lei Zhu (Orthopaedic Surgery)
For lengthening irregular bones, such as calcaneus, there are few reports in the literature. This study aimed to introduce the treatment strategy and preliminary outcomes for calcaneus shortening using calcaneal body lengthening. From January 2017 to January 2022, calcaneal lengthening was conducted for three patients (two males and one female) who suffered from traumatic calcaneal shortening. The Achilles tendon was lengthened in one patient. After osteotomy of the calcaneus, an Ilizarov frame was used to gradually (1 mm/day) distract the calcaneal fragment. The lengthening procedure was stopped when the calcaneal height and length were restored based on radiography. The fixator was removed after bone union. The average follow‐up length was 18 months (range, 14–24 months). X‐ray was used for radiological assessments. Patients reported satisfaction using the 100‐mm visual analog scale (VAS). Clinical outcome was evaluated following the American Orthopedic Foot and Ankle score. All data were assessed by two physicians blind to clinical assessments. The wound healed primarily in three cases. The bone got solid union without refracture and malunion. The distraction time was 30 days (range, 25–45 days). The fixation time was 113.3 days (average, 80–150 days). Calcaneal lengthening was 26 mm (range, 15–43 mm). The height and length of the calcaneus were restored nearly to the same as the opposite foot. The mean preoperative calcaneal pitch angle increased from 2.6 degrees to an average of 19.0 degrees after the surgery. The AOFAS score increased from 60.0 to 86.0. One patient experienced pin infection. The infection healed after changing the dressing. Calcaneal lengthening using an Ilizarov external fixator is a preferable technique to restore the length and height of the calcaneus and can achieve satisfactory foot function.